The degree to which the supervisory model contributes to enabling the schools of the Oasis Education Office in Jeddah to practice procedural research from the point of view of school employees - Shuwaylan, Afra Ahmad; Abualella, Hana Mohammed; Al-Asmari, Aisha Ali; Ahmed, Rasha Ezzat; Al-Jehani, Hend Hdyban (Journal of Educational and Psychological Sciences, 2025)
The study aimed to determine the extent to which the supervisory model contributes to empowering the staff of the Waha Education Office in Jeddah with skills in preparing action research, their attitudes towards practicing action research from their perspective, and the impact of variables (qualification, experience, training courses in action research) on their responses. The study employed a descriptive survey methodology, using a questionnaire consisting of 28 statements distributed across two axes, which was administered to a sample of 220 staff members from the Waha Education Office in Jeddah. The results showed a high contribution of the supervisory model in empowering the staff with skills in preparing action research, as well as in their attitudes towards practicing it. Statistically significant differences were found between the responses of different sample categories regarding the contribution of the supervisory model to research preparation skills, attributed to the variables of (qualification, training courses, and experience), favoring those with experience (5-9 years), those with (two or more training courses), and those with academic qualifications (Bachelor’s and higher). Additionally, significant differences were found in their attitudes towards practicing action research attributed to (training courses, years of experience), favoring those with (10 years or more of experience) and those who had (one to two training courses). However, no differences were found in the degree of attitude towards practicing action research attributed to academic qualification. The study provided several recommendations, the most important of which is the necessity of adopting action research as a key method within the supervisory model for self-evaluation processes to empower schools to improve various technical, administrative, and teaching operations.